PENGARUH PEMBERIAN PUPUK KOTORAN KAMBING TERHADAP PERTUMBUHAN BAYAM MERAH (Amaranthus tricolor L.) - Nurin Sarofina (Program Studi Pendidikan Biologi, 2021)
Abstract: Red Spinach is one of the vegetables that can be relied on to meet the needs of vitamins and minerals which is relatively easy. To get good plant growth, a medium is needed, one of which is goat manure. The aim of the researchers was to determine the effect of goat manure on the growth of red spinach (Amaranthus tricolor L) with a variety of different treatments, namely: A (1500 g soil), B (75 g goat manure + 1500 g soil), C (100 g goat manure + 1500 g soil), D (125 g goat manure + 1500 g soil), E (150 g goat manure + 1500 g soil), with four replications for each treatment. Parameters measured were red spinach plant height, number of leaves, and leaf width. This study used a completely randomized design method (CRD). To determine whether there is an effect of using differences between treatments, it is done by using the F-table test of 5% and 1%. The results of the study were very significant differences in the treatment of plant height, number of leaves, and leaf width. Of the five treatments, the optimal average growth rate was treatment E with the addition of E (goat manure 150 g + soil 1500 g).